2009
DOI: 10.1007/s00705-009-0522-6
|View full text |Cite
|
Sign up to set email alerts
|

Genetic variability and phylogenetic analysis of hosta virus X

Abstract: Triple gene block 1 (TGB1) and coat protein (CP) sequences of 30 hosta virus X (HVX) isolates from Tennessee (TN), USA, were determined and compared with available sequences in GenBank. The CPs of all known HVX isolates, including those from TN, shared 98.3-100% and 98.2-100% nucleotide and amino acid sequence identity, respectively, whereas TGB1 shared 97.4-100% nucleotide and 97-100% amino acid sequence identity. TGB1 of TN isolates were all longer by one codon from that of a Korean isolate, which is the onl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
13
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 24 publications
2
13
0
Order By: Relevance
“…It is not likely that the CymMV subgrouping based on nt sequences reflects specific host-plant features, since phylogenetic tree analysis showed no correlation between isolates of each subgroup and plant species that they were isolated from or between isolates of each subgroup and the geographical origins. In accordance with these observations, the clustering of CymMV isolates confirmed previous CP analysis data for the trees obtained from the CP alignment of CymMV or other potexviruses [22][23][24]. Some isolates of CymMV showed significantly variability at the C-termini of the CP.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…It is not likely that the CymMV subgrouping based on nt sequences reflects specific host-plant features, since phylogenetic tree analysis showed no correlation between isolates of each subgroup and plant species that they were isolated from or between isolates of each subgroup and the geographical origins. In accordance with these observations, the clustering of CymMV isolates confirmed previous CP analysis data for the trees obtained from the CP alignment of CymMV or other potexviruses [22][23][24]. Some isolates of CymMV showed significantly variability at the C-termini of the CP.…”
Section: Discussionsupporting
confidence: 89%
“…Some isolates of CymMV showed significantly variability at the C-termini of the CP. A similar observation was found in the CP analysis of Hosta virus X (HVX), which showed that the C-terminal region of the CP in HVX isolates is the most variable region of this protein [24].…”
Section: Discussionmentioning
confidence: 54%
“…This indicated that PVX was under strong selection pressure against changes in the structures of PVX proteins and even nt sequences. A similar situation occurs in the case of another potexvirus, hosta virus X, whose isolates share identities of 98.3-100% at nt level and 98.6-100% at aa level [23]. Therefore, the variability of viruses transmitted via infected vegetative propagating materials may not be higher than aphid-borne or seed-borne viruses.…”
Section: Discussionmentioning
confidence: 87%
“…HVX has been subsequently reported in Korea (Ryu et al 2002), the Netherlands (Verhoeven et al 2006), Poland (Cajza and Zielinska 2007) and France (Jullien and Chauvel 2007) and has become a problem to hosta growers. HVX has been confirmed to be a distinct species of the genus Potexvirus in the family Flexiviridae (Park and Ryu 2003;Fajolu et al 2009). In nature, this virus infects only hostas and is most likely to be spread by vegetative propagation or mechanical contact (Currier and Lockhart 1996), and through seed (Ryu et al 2006).…”
mentioning
confidence: 98%